Camera lucida: Reflections on photography - Barthes, Roland; Howard, Richard (London vintage books, 2000)
Examining the themes of presence and absence, the relationship between photography and theatre, history and death, these 'reflections on photography' begin as an investigation into the nature of photographs. Then, as Barthes contemplates a photograph of his mother as a child, the book becomes an exposition of his own mind. About The Author: About The Author: Roland Barthes was born in 1915 and studied French literarture and classics at the University of Paris. After teaching French at universities in Romania and Egypt, he joined the Centre National de Recherche Scientifique, where he devoted himself to research in sociology and lexicology.